The pathogenecity of H5N1 highly pathogenic Avian Influenza (HPAI) virus clade 2.3.2. in Indonesian indigenous chicken by contact tranmission with infected duck - Damayanti, R.; Wiyono, A.; Nuradji, H.; Cahyono, M. I. (Diponegoro University, 2017)
An experimental transmission study was conducted using nine healthy Indonesian indigenous chickens placed together with two 30 days old ducks which were experimentally infected with H5N1 HPAI clade 2.3.2 virus in the Biosafety Laboratory Level 3 (BSL-3) facilities. The aim of the study was to find out the pathogenicity of H5N1 HPAI virus clade 2.3.2 in Indonesian indigenous chickens. The study showed that within twenty four hours rearing, the chickens were exhibited mild clinical signs and by 48 hours, all of the chickens died, whereas the ducks survived but with severe clinical signs. The H5N1 HPAI virus has been successfully isolated from chickens and ducks swabs, confirming that those animals were infected by the virus. Histologically, the infected chicken encountered with severe inflammation reaction namely non suppuratives encephalitis, tracheitis, myocarditis, interstitial pneumonia, hepatitis, proventriculitis, enteritis, pancreatitis, nephritis and bursitis. Necrotizing spleen and pancreas were also prominent. Viral antigen was detected by immunohistochemistry staining in various affected visceral organs. This suggests that Indonesian indigenous chickens were susceptible to H5N1 HPAI virus clade 2.3.2 and it can be transmitted easily to Indonesian indigenous chickens by contact transmission with infected ducks.